2020
DOI: 10.1002/cjp2.170
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis‐free deep survival learning applied to the tumour microenvironment in gastric cancer

Abstract: The biological complexity reflected in histology images requires advanced approaches for unbiased prognostication. Machine learning and particularly deep learning methods are increasingly applied in the field of digital pathology. In this study, we propose new ways to predict risk for cancer-specific death from digital images of immunohistochemically (IHC) stained tissue microarrays (TMAs). Specifically, we evaluated a cohort of 248 gastric cancer patients using convolutional neural networks (CNNs) in an end-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…In our study, scRNA-seq enabled lineage-based comparisons of the TME between these histological subtypes, leading to the discovery of increased plasma cells in diffusetype GCs. Compared to T-cells, there are fewer studies on B-cell and plasma cell populations in GC (82,83). Derks et al, reported a higher proportion of tertiary lymphoid structures in GS tumors with enrichment of B-cells and CD4 T-cells (84).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, scRNA-seq enabled lineage-based comparisons of the TME between these histological subtypes, leading to the discovery of increased plasma cells in diffusetype GCs. Compared to T-cells, there are fewer studies on B-cell and plasma cell populations in GC (82,83). Derks et al, reported a higher proportion of tertiary lymphoid structures in GS tumors with enrichment of B-cells and CD4 T-cells (84).…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study dealing with the prediction of cancer-specific death in GC. Meier et al [41] analysed HE and immunohistochemically stained tissue to identify survival-related features and predict the risk of cancer-specific death. As indicators for immunogenicity and aggressive growth, they looked at immune cell markers (CD8, CD20, CD68) and a proliferation marker (Ki-67).…”
Section: Prognosismentioning
confidence: 99%
“…This model could effectively identify CRC patients and predict the survival benefits from curative CRC surgery[ 140 , 141 ], which was a quantum leap in non-invasive screening. Several immune markers, including CD8, CD20, and CD68, combined with the proliferation marker Ki-67 by CNN showed great prognostic value in GC[ 135 ]. DNA aneuploidy, tumor-stroma ratio, and RNA sequencing were also proven to have great value in clinical prediction that were evacuated by ANN[ 142 - 144 ].…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%